Nanoporous Co3W-WNi4 / Ni composite electrode, its preparation method and application

CN118222875BActive Publication Date: 2026-10-23JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410326947.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-21
Publication Date
2026-10-23
Estimated Expiration
2044-03-21

AI Technical Summary

Technical Problem

[0003]固溶体合金原子分布随机,难以建立催化材料结构-性能关系,不能准确揭示催化反应机制,且纳米结构的固溶体合金材料热力学不稳定,在电化学过程中会发生结构粗化、失活等现象,不能满足电极系统对耐久性的需求

Benefits of technology

[0018]本公开所述W桥连的Co3W-WNi4/Ni双金属间化合物无缝集成在柱状的纳米多孔Ni骨架上,大孔道尺寸约为100nm,小孔尺寸约为5nm。其中,大孔道促进电解液和气体分子的质量传输,小孔结构提高电极材料的比表面积,暴露多的活性位点于电解液中,三维互连的Ni网络有利于催化反应过程中的电子转移。Co3W-WNi4界面处的W位点有助于析氢反应过程中水的解离,解离的H和OH中间体分别吸附在邻近的Co和Ni位点上,H中间体耦合生成H2。另外,W位点同时促进氢氧化反应过程中水的形成,提高氢氧化反应动力学。因此,纳米多孔Co3W-WNi4/Ni复合电极具有优异的析氢反应和氢氧化反应性能,为水电解池和氢燃料电池的大规模商业化应用提供了材料基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118222875B_ABST
    Figure CN118222875B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a nanoporous Co3W-WNi4 / Ni composite electrode and a preparation method thereof and electrocatalytic applications thereof. The preparation is as follows: a, cleaning high-purity Ni, Co and W metal sheets, etching the oxides on the surface of the Al metal sheet, and then washing with ultrapure water several times; b, weighing each metal according to the atomic ratio of Ni, Co, W and Al 10:6:4:80, and melting the alloy; c, placing the alloy metal ingot in the sample tube of the high-vacuum spin-chilling device to obtain a thin alloy strip with a thickness of about 80 μm; d, placing the thin alloy strip in a 6M KOH solution saturated with N2 at 70 DEG C, etching and then cleaning to obtain a nanoporous Co3W-WNi4 / Ni composite electrode. The Co3W-WNi4 / Ni bimetallic intermetallic compound is seamlessly integrated on the columnar nanoporous Ni skeleton, the structure of the double-mode pores increases the specific surface area of the electrode material, increases the number of active sites, and promotes mass transfer and electron transport, thereby improving the kinetics of the hydrogen evolution reaction and the hydrogen oxidation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to nanoporous Co3W-WNi4 / Ni composite electrodes, their preparation methods, and applications. Background Technology

[0002] Hydrogen energy is a clean and efficient secondary energy source that can serve as a medium for energy interconnection. Electrocatalytic water splitting, driven by renewable energy sources (such as solar or wind power), produces hydrogen, converting electrical energy into chemical energy and storing it. This is then coupled with a hydrogen fuel cell, where hydrogen reacts with oxygen to produce pollution-free water, converting chemical energy back into electrical energy. This system, using hydrogen and water as carriers, represents a highly feasible energy conversion pathway. The hydrogen evolution reaction (HEP) and hydrogen oxidation reaction are crucial half-reactions in water electrolysis and hydrogen fuel cells. Although phosphorus (Pt) is the most intrinsically active catalytic material, its abundance is low, its cost is high, and its activity in alkaline electrolytes is 2-3 orders of magnitude lower than in acidic electrolytes. Therefore, the development of highly efficient non-precious metal-based catalytic materials for the HEP and hydrogen oxidation reactions, and the construction of electrode systems with high conductivity, high specific surface area, and high intrinsic catalytic activity, are current research hotspots.

[0003] Solid solution alloys have random atomic distributions, making it difficult to establish structure-property relationships in catalytic materials and accurately reveal catalytic reaction mechanisms. Furthermore, nanostructured solid solution alloys are thermodynamically unstable, exhibiting structural coarsening and deactivation during electrochemical processes, failing to meet the durability requirements of electrode systems. In contrast, intermetallic compounds with well-defined atomic structures can regulate the adsorption energy of reaction intermediates through electron transfer or coordination / strain effects arising from differences in electronegativity between elements. Moreover, their ordered crystal structure provides intrinsic thermodynamic stability, a characteristic that promises to solve the lifespan problem of electrode materials. Based on these considerations, we propose a research approach using bimetallic compounds to catalyze hydrogen evolution and hydrogen oxidation reactions, aiming to develop low-cost, highly active, and long-life catalytic materials. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, this disclosure provides a nanoporous Co3W-WNi4 / Ni composite electrode, its preparation method, and its electrocatalytic application.

[0005] According to a first aspect of this disclosure, a method for preparing a nanoporous Co3W-WNi4 / Ni composite electrode is provided, characterized by comprising the following steps:

[0006] a. Cleaning the metal: Soak and clean the high-purity Ni, Co, and W metal sheets in acetone and dilute hydrochloric acid in sequence, then use dilute NaOH solution to corrode the oxides on the surface of the Al metal sheet, and then clean the metal sheets several times with ultrapure water. After that, place the cleaned metal sheets in a vacuum drying oven to dry for later use.

[0007] b. Melting the alloy ingot: Weigh each metal Ni, Co, W, and Al according to an atomic ratio of 10:6:4:80, with a total mass of 8-12g; place the weighed metals in an electric arc furnace and melt the alloy under an argon atmosphere, repeating the arc melting 6-10 times to obtain a metal ingot with uniform alloy composition; after the alloy metal ingot cools to room temperature, remove the alloy metal ingot, which is silvery-white.

[0008] c. Preparation of thin strips: The oxide layer on the surface of the alloy metal ingot is polished with sandpaper and the alloy metal ingot is cleaned with ethanol; the alloy metal ingot is placed in the sample tube of a high vacuum spin quenching device, and the alloy metal ingot is melted under an argon atmosphere, and then sprayed onto a copper roller with a rotation speed of 2000r to obtain a thin alloy strip with a thickness of about 80μm.

[0009] d. Chemical dealloying: The thin alloy strip is placed in a 6M KOH solution saturated with N2 at 70°C for etching. After a certain period of time, when no more bubbles are generated on the surface of the thin alloy strip, the thin alloy strip is washed with ultrapure water multiple times to obtain a nanoporous Co3W-WNi4 / Ni composite electrode.

[0010] Preferably, the alloy metal ingot in step b has a Ni composition. 10 Co6W4Al 80 (at%).

[0011] Preferably, the rotational speed of the copper roller in step c is 2000 r.

[0012] Preferably, in step d, the thin alloy strip is placed in a 6M KOH solution saturated with N2 at 70°C for 3 hours.

[0013] According to a second aspect of this disclosure, a nanoporous Co3W-WNi4 / Ni composite electrode is provided.

[0014] According to a third aspect of this disclosure, an application of a nanoporous Co3W-WNi4 / Ni composite electrode is provided, characterized in that the composite electrode is used as a hydrogen evolution reaction electrode and a hydroxide reaction electrode.

[0015] The principle of this disclosed technical solution is:

[0016] The precursor alloy ingot is prepared by alloying and eutectic template dealloying methods. The process is simple and can be scaled up. First, high-purity metals Ni, Fe, Co, and W are melted into precursor alloy ingots Ni in an electric arc furnace. 10 Co6W4Al 80 The material is then prepared into thin strips using a high-vacuum spin quenching system, and finally, Al is removed by chemical dealloying with alkaline solution to form a nanoporous Co3W-WNi4 / Ni bimetallic compound / metal composite electrode. The Co3W-WNi4 / Ni bimetallic compound is seamlessly integrated onto a columnar nanoporous Ni framework. The dual-mode pore structure increases the specific surface area of ​​the electrode material, enhances the number of active sites, and promotes mass transfer and electron transport. Because the bimetallic compound has multiple electrocatalytic active sites, reaction intermediates transfer between different sites. The W site at the interface facilitates water dissociation / formation, while H and OH intermediates are adsorbed onto adjacent Co and Ni sites, respectively, collectively improving the kinetics of the hydrogen evolution reaction and the hydroxide ionization reaction. Experimental results confirm that this electrode exhibits excellent performance in both hydrogen evolution and hydroxide ionization reactions.

[0017] The beneficial effects of this disclosed technical solution are:

[0018] The W-bridged Co3W-WNi4 / Ni bimetallic compound disclosed herein is seamlessly integrated onto a columnar nanoporous Ni framework, with macropores approximately 100 nm in size and micropores approximately 5 nm in size. The macropores facilitate mass transport between the electrolyte and gas molecules, while the micropore structure increases the specific surface area of ​​the electrode material, exposing more active sites in the electrolyte. The three-dimensional interconnected Ni network is beneficial for electron transfer during the catalytic reaction. The W sites at the Co3W-WNi4 interface facilitate the dissociation of water during the hydrogen evolution reaction. The dissociated H and OH intermediates are adsorbed onto adjacent Co and Ni sites, respectively, with the H intermediate coupling to generate H2. Furthermore, the W sites simultaneously promote water formation during the hydrogen oxidation reaction, enhancing the kinetics of the hydrogen oxidation reaction. Therefore, the nanoporous Co3W-WNi4 / Ni composite electrode exhibits excellent hydrogen evolution and hydrogen oxidation reaction performance, providing a material basis for the large-scale commercial application of water electrolyzers and hydrogen fuel cells. Attached Figure Description

[0019] The above and other features, advantages, and aspects of the embodiments of this disclosure will become more apparent from the accompanying drawings and the following detailed description. The drawings are provided for a better understanding of the present invention and are not intended to limit the scope of this disclosure. In the drawings, the same or similar reference numerals denote the same or similar elements, wherein:

[0020] Figure 1 Scanning electron microscope (SEM) images of nanoporous Co3W-WNi4 / Ni in embodiments of this disclosure;

[0021] Figure 2Energy dispersive spectroscopy (EDS) diagrams of nanoporous Co3W-WNi4 / Ni in embodiments of this disclosure;

[0022] Figure 3 X-ray diffraction (XRD) patterns of nanoporous Co3W-WNi4 / Ni according to embodiments of this disclosure;

[0023] Figure 4 High-resolution transmission electron microscopy (HRTEM) images of nanoporous Co3W-WNi4 / Ni in embodiments of this disclosure;

[0024] Figure 5 Transmission electron microscopy images and elemental distribution diagrams of nanoporous Co3W-WNi4 / Ni according to embodiments of this disclosure;

[0025] Figure 6 The present invention discloses the hydrogen evolution reaction polarization curves of nanoporous Co3W-WNi4 / Ni in 1MKOH electrolyte;

[0026] Figure 7 Tafel diagram of the hydrogen evolution reaction of nanoporous Co3W-WNi4 / Ni in the embodiments of this disclosure;

[0027] Figure 8 Impedance spectra of nanoporous Co3W-WNi4 / Ni in 1M KOH electrolyte according to embodiments of this disclosure;

[0028] Figure 9 The hydrogen evolution reaction stability of nanoporous Co3W-WNi4 in the embodiments of this disclosure;

[0029] Figure 10 The present invention discloses the hydrogenation reaction polarization curves of nanoporous Co3W-WNi4 in 0.1 MkOH electrolyte;

[0030] Figure 11 The hydrogenation reaction stability of nanoporous Co3W-WNi4 in the embodiments of this disclosure. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments of this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure.

[0032] Example 1

[0033] A method for preparing a nanoporous Co3W-WNi4 / Ni composite electrode, comprising the following steps:

[0034] 1) Cleaning the metal: Soak and clean the high-purity Ni, Co, and W metal sheets in acetone and dilute hydrochloric acid in sequence. Use dilute NaOH solution to corrode the oxides on the surface of the Al metal sheet. Then rinse the metals several times with ultrapure water and place them in a vacuum drying oven to dry for 10 hours.

[0035] 2) Melting the alloy ingot: Weigh each metal according to the atomic ratio of Ni, Co, W, and Al of 10:6:4:80, weighing 1.50g of Ni sheet, 0.90g of Co sheet, 1.89g of W sheet, and 5.74g of Al sheet; place the weighed metals in an electric arc furnace and melt the alloy under an argon atmosphere, repeating the arc melting 6-10 times to achieve uniformity of the alloy composition; after the metal ingot cools to room temperature, remove the alloy, which is silvery-white. The composition of the alloy ingot is Ni. 10 Co6W4Al 80 (at%).

[0036] 3) Preparation of thin strips: The oxide layer on the surface of the alloy ingot is polished with sandpaper and the alloy ingot is cleaned with ethanol. The alloy ingot is placed in the sample tube of a high-vacuum spin quenching device, and the alloy ingot is melted under an argon atmosphere. Then it is sprayed onto a copper roller with a rotation speed of 2000 r to obtain a thin alloy strip with a thickness of about 80 μm.

[0037] 4) Chemical dealloying: The thin alloy strip was placed in a 6M KOH solution saturated with N2 at 70℃. Vigorous gas was generated on the surface of the strip. After 3 hours, no more bubbles were generated on the sample surface. The alloy was washed with ultrapure water multiple times to obtain a nanoporous Co3W-WNi4 / Ni composite electrode.

[0038] The morphology and structural characterization results of the composite electrode are as follows:

[0039] Figure 1 This is a scanning electron microscope image of a nanoporous Co3W-WNi4 / Ni electrode. The electrode exhibits a columnar nanoporous structure with pore sizes of approximately 5 nm and macropore sizes of approximately 100 nm. The macropores facilitate mass transport between the electrolyte and gas molecules, while the micropore structure increases the specific surface area of ​​the electrode material, exposing more active sites in the electrolyte. The three-dimensionally interconnected Ni network is beneficial for electron transfer during the catalytic reaction. Figure 2 This indicates that the atomic ratio of Ni, Co, W, and Al in the nanoporous Co3W-WNi4 / Ni is 59:30:4:7. Figure 3In the XRD pattern, the characteristic peaks at 40.8°, 43.9°, 46.5°, and 48.6° correspond to the (200), (002), (201), and (102) crystal planes of Co3W, respectively; the characteristic peaks at 43.5°, 50.3°, and 51.4° correspond to the (211), (130), and (002) crystal planes of WNi4, respectively; and the characteristic peaks at 44.3°, 51.0°, and 76.0° correspond to the (111), (200), and (220) crystal planes of Ni, respectively. This proves that the electrode is composed of intermetallic compounds of Ni, Co3W, and WNi4. Figure 4 The high-resolution transmission electron microscopy (TEM) images further characterized the atomic structure of the nanoporous Co3W-WNi4 / Ni. 0.208 nm corresponds to the (211) interplanar spacing of WNi4, 0.195 nm to the (201) interplanar spacing of Co3W, and 0.203 nm to the (111) interplanar spacing of Ni. Figure 5 The transmission electron microscopy images and corresponding elemental distribution results show that Ni, Co, and W are uniformly distributed on the Ni ligament.

[0040] Example 2

[0041] The hydrogen evolution reaction performance of the composite electrode material obtained in Example 1 was tested in a three-electrode system. In 1 MKOH, the nanoporous Co3W-WNi4 / Ni composite electrode material was used as the working electrode, a carbon rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The specific test procedure is as follows:

[0042] 1) Within a voltage range of 0 to -0.3V (relative to the reversible hydrogen electrode), at 1mV s -1 The scanning speed was used to test the polarization curve of the hydrogen evolution reaction;

[0043] 2) Test its impedance spectrum at -0.1V, with an amplitude of 5mV and a frequency of 10mHz to 100kHz;

[0044] 3) Within a voltage window of -0.95 to -0.85V (relative to the reference electrode), at 40, 45, 50, and 55 mV s -1 The CV curves of the nanoporous electrode were measured at the scanning rate, and its electrochemical active area was evaluated based on its double-layer capacitance value.

[0045] 4) The stability of the nanoporous Co3W-WNi4 / Ni electrode was tested for 1000 hours at a voltage of -0.1V (relative to the reversible hydrogen electrode).

[0046] The characterization results of the hydrogen evolution reaction performance of the nanoporous Co3W-WNi4 / Ni electrode material are as follows:

[0047] Figure 6The hydrogen evolution reaction polarization curves of nanoporous Co3W-WNi4 / Ni bimetallic / metal composite electrodes, nanoporous WNi4 / Ni monometallic / metal composite electrodes, Co / Ni solid solution electrodes, Ni electrodes, and commercially available Pt / C supported on porous Ni (Pt / C / Ni) electrodes were compared. At an overpotential of 200 mV, the Co3W-WNi4 / Ni electrode achieved a polarization rate of ~1.45 Acm. -2 The current density is far greater than that of WNi4 / Ni (~0.45 A cm⁻¹). -2 ), Co / Ni (~0.11A cm) -2 Pt / C / Ni (~0.85Acm) -2 The current density of the electrodes. Furthermore, such as... Figure 7 As shown, the Tafel slope of the nanoporous Co3W-WNi4 / Ni electrode is as low as ~42 mV dec. -1 The efficiency was significantly lower than that of other comparative electrode materials, indicating that this electrode possesses excellent hydrogen evolution reaction performance. Electrochemical impedance spectroscopy analysis further revealed the reaction kinetics, such as... Figure 8 As shown, the charge transfer resistance of the nanoporous Co3W-WNi4 / Ni electrode is ~1.9Ω, lower than that of other comparative electrode materials, demonstrating that the nanoporous Co3W-WNi4 / Ni electrode possesses fast reaction kinetics. A stability test was conducted on this electrode at a potential of -100mV (relative to the reversible hydrogen electrode) for 1000 hours, as shown... Figure 9 As shown, the corresponding current density is maintained at ~420 mA / cm². -2 Furthermore, the absence of significant fluctuations demonstrates the excellent stability of this electrode material in the hydrogen evolution reaction. This is because the nanoporous structure is stable, and the active phase of the intermetallic compound Co3W-WNi4 bimetallic compound nanoparticles is seamlessly integrated onto the robust Ni framework, forming a coherent interface that enhances the electrochemical stability of the electrode.

[0048] Example 3

[0049] The performance of the composite electrode material obtained in Example 1 in the hydroxide reaction under 0.1 MkOH saturated with hydrogen was tested. The specific test procedure is as follows:

[0050] 1) The polarization curve of the hydroxide reaction was tested, with a voltage range of 0–0.35 V (relative to the reversible hydrogen electrode) and a scan rate of 2 mV / s. -1 ;

[0051] 2) Test its impedance at 0.03V, with an amplitude of 5mV and a frequency of 10mHz to 100kHz;

[0052] 3) Cyclic voltammetry curves of the nanoporous Co3W-WNi4 / Ni electrode were measured for 1000 cycles within the voltage range of -0.05 to 0.15 V (relative to the reversible hydrogen electrode) at a scan rate of 200 mV / s. -1 , used to characterize its stability.

[0053] The characterization results of the hydroxide reaction performance of the nanoporous Co3W-WNi4 / Ni electrode material are as follows:

[0054] Figure 10 The oxidation reaction polarization curves of nanoporous Co3W-WNi4 / Ni, WNi4 / Ni, Co / Ni, and Ni electrodes were compared. Co3W-WNi4 / Ni achieved a polarization of ~31.4 mA / cm² at 0.22 V. -2 The current density is far greater than that of WNi4 / Ni (~19.8 mA / cm). -2 ), Co / Ni (~16.2 mAcm) -2 ) and Ni (~13.6 mA cm -2 Additionally, such as Figure 11 As shown, the current density of the nanoporous Co3W-WNi4 / Ni did not decrease significantly after 1000 cycles of cyclic voltammetry stability testing, indicating that it has excellent stability in the hydroxide reaction.

[0055] In summary, the W-bridged Co3W-WNi4 / Ni bimetallic compound disclosed herein is seamlessly integrated onto a columnar nanoporous Ni framework, with macropores of approximately 100 nm and micropores of approximately 5 nm. The macropores facilitate mass transport between the electrolyte and gas molecules, while the micropore structure increases the specific surface area of ​​the electrode material, exposing more active sites in the electrolyte. The three-dimensional interconnected Ni network is beneficial for electron transfer during the catalytic reaction. The W sites at the Co3W-WNi4 interface facilitate the dissociation of water during the hydrogen evolution reaction, with the dissociated H and OH intermediates adsorbed onto adjacent Co and Ni sites, respectively, and the H intermediate coupling to generate H2. Furthermore, the W sites simultaneously promote water formation during the hydrogen oxidation reaction, enhancing the kinetics of the hydrogen oxidation reaction. Therefore, the nanoporous Co3W-WNi4 / Ni composite electrode exhibits excellent hydrogen evolution and hydrogen oxidation reaction performance, providing a material basis for the large-scale commercial application of water electrolyzers and hydrogen fuel cells.

[0056] The above embodiments are preferred embodiments of this disclosure, but the embodiments of this disclosure are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of this disclosure shall be considered equivalent substitutions and shall be included within the protection scope of this disclosure.

Claims

1. A method for preparing a nanoporous Co3W-WNi4 / Ni composite electrode, characterized in that, Includes the following steps: a. Cleaning the metal: Soak the high-purity Ni, Co, and W metal sheets in acetone and dilute hydrochloric acid in sequence, then use dilute NaOH solution to corrode the oxides on the surface of the Al metal sheet, and then wash all the metal sheets several times with ultrapure water. After that, place all the cleaned metal sheets in a vacuum drying oven to dry for later use. b. Melting the alloy ingot: Weigh each metal Ni, Co, W, and Al according to an atomic ratio of 10:6:4:80, with a total mass of 8-12g; place the weighed metals in an electric arc furnace and melt the alloy under an argon atmosphere, repeating the arc melting 6-10 times to obtain an alloy metal ingot with uniform composition; after the alloy metal ingot cools to room temperature, remove the alloy metal ingot, which is silvery-white in color. c. Preparation of thin strips: The oxide layer on the surface of the alloy metal ingot is polished with sandpaper and the alloy metal ingot is cleaned with ethanol; the alloy metal ingot is placed in the sample tube of a high vacuum spin quenching device, and the alloy metal ingot is melted under an argon atmosphere, and then it is sprayed onto a copper roller with a rotation speed of 2000 rpm to obtain a thin alloy strip with a thickness of 80 μm. d. Chemical dealloying: The thin alloy strip is placed in a 6M KOH solution saturated with N2 at 70 °C for etching. After a certain period of time, when no more bubbles are generated on the surface of the thin alloy strip, the thin alloy strip is washed with ultrapure water multiple times to obtain a nanoporous Co3W-WNi4 / Ni composite electrode.

2. The method for preparing the nanoporous Co3W-WNi4 / Ni composite electrode according to claim 1, characterized in that: The alloy metal ingot described in step b has a composition of Ni at% 10 Co6W4Al 80 .

3. The method for preparing the nanoporous Co3W-WNi4 / Ni composite electrode according to claim 1, characterized in that: In step d, the thin alloy strip is placed in a 6 M KOH solution saturated with N2 at 70 °C for 3 hours.

4. A nanoporous Co3W-WNi4 / Ni composite electrode obtained by the preparation method according to any one of claims 1-3.

5. The application of the nanoporous Co3W-WNi4 / Ni composite electrode according to claim 4, characterized in that, The composite electrode is used as a hydrogen evolution reaction electrode or a hydroxide reaction electrode.

Citation Information

Patent Citations

  • Preparation method of nano-porous metal or alloy

    CN111254309A

  • Preparation method and application of multi-component intermetallic compound nanoparticles on layered metal network

    CN115652328A